(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Education is one of the important contents in Ho Chi Minh’s ideology to contribute to solving the requirements of Vietnam’s history and society in the early modern period. His educational ideology has been expressed quite abundantly and profoundly through issues such as: purposes, roles, content, methods, etc. in people education. That ideology has still brought out the breath of the era to this day, and has theoretical and practical significance, directing the process of educational development and innovation in Vietnam today.